Yeast reveal a “druggable” Rsp5/Nedd4 Network that Ameliorates α–Synuclein Toxicity in Neurons - Tardiff, Daniel F. (2013)
α–synuclein (α-syn) is a small lipid binding protein implicated in several neurodegenerative diseases, including Parkinson’s disease, whose pathobiology is conserved from yeast to man. There are no therapies targeting these underlying cellular pathologies, or indeed those of any major neurodegenerative disease. Using unbiased phenotypic screens as an alternative to target-based approaches, we discovered an N-aryl benzimidazole (NAB) that strongly and selectively protected diverse cell-types from α-syn toxicity. Three chemical genetic screens in wild-type yeast cells established that NAB promoted endosomal transport events dependent on the E3 ubiquitin ligase, Rsp5/Nedd4. These same steps were perturbed by α–syn itself. Thus, NAB identifies a druggable node in the biology of α-syn that can correct multiple aspects of its underlying pathology, including dysfunctional endosomal and ER-to-Golgi vesicle trafficking.